Analisis Sistem Paperless Office pada PT Duraquipt Cemerlang - Afina Diah Pratiwi; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The development of information technology encourages companies to carry out digital transformation in various operational aspects, including document management and administrative processes. This research aims to analyze the effectiveness of the implementation of a paperless office system at PT Duraquipt Cemerlang, identify challenges faced during the digital transition process, and evaluate its impact on operational efficiency and employee productivity. The method in this study uses a descriptive qualitative approach, data collected through observation, interviews, and internal documentation. The results showed that the implementation of a paperless office system improved work process efficiency, saved operational costs, and reduced paper usage. Successful implementation is supported by good information technology infrastructure and employee training. However, challenges faced include differences in user adaptation levels, negative perceptions of digital systems, and the need for increased digital literacy. The results of this study are expected to serve as a reference for other companies in implementing digital systems as part of a strategy to improve operational performance and work innovation.